Pengaruh Active Recovery terhadap Denyut Nadi Pemulihan Atlet Sepak Bola Usia 9 Tahun di SSB Kancil Mas Karawang - Zulyar Firdaus Farthurohman Ahmad; Rona Agil Pratama; Muhanmmad Abizar Revaldi; Muksin Muksin; Muhammad Nandi Agustin; M. Arief Setiawan; Miftahudin Sigit (Jurnal Porkes, 2026)
This study aimed to examine the effect of active recovery on heart rate recovery in 9-year-old soccer athletes at SSB Kancil Mas Karawang. A pre-experimental design with a one-group pretest–posttest approach was employed. The sample consisted of 15 male soccer athletes selected through total sampling. Heart rate was measured immediately after the main training session (pretest) and again after 10–15 minutes of active recovery comprising light jogging and active stretching (posttest). Data analysis included descriptive statistics, the Shapiro–Wilk normality test applied to the pretest and posttest data, a paired sample t-test, and Cohen's d effect size. Results showed that mean heart rate decreased significantly from 163.47 ± 7.32 bpm (pretest) to 118.93 ± 6.14 bpm (posttest), a mean difference of 44.53 bpm (95% CI 40.27–48.79). The paired sample t-test produced t(14) = 22.41, p < 0.001, and Cohen's d = 5.79, indicating a very large effect, with all 15 athletes showing a reduction. Within this population and these study conditions, active recovery was highly effective in accelerating heart rate recovery in young soccer athletes and may serve as a practical post-exercise recovery modality in youth football training programs.